A Numerical Method of the Ramm Integral Equation (Journal of Computational Mathematics, 2021)
A numerical method for solving the ill-posed Ramm integral equation is presented in this paper. It is found that the method is stable and more accurate. Particularly, when the given data is contaminated by noise, satisfactory results are obtained by using the algorithm of this paper.